Comments on the Lithic Technology and Geochronology of the Goodson Rock Shelter. (2nd April 2020) - Huckell, Bruce B.; Vance Haynes, C.; Holliday, Vance T.
ABSTRACT: In a recent article published in PaleoAmerica, authors Metin I. Eren, David J. Meltzer, and Brian M. Andrews describe a set of Clovis-like artifacts recovered from an Archaic context at Goodson Rock Shelter, Oklahoma. With this discovery, they conclude that we cannot reliably recognize true Clovis assemblages and sites, especially caches, without true Clovis points, and that we should not consider other technological characteristics such as overshot flaking and prismatic blade manufacture as unequivocally representing Clovis. In this essay, we propose two additional working hypotheses that potentially explain the reported record from Goodson Rock Shelter: (1) the assemblage is not a Clovis look-alike at all; or (2) the assemblage is Clovis, but mixed with artifacts from younger occupations. We respectfully call on Eren, Meltzer, and Andrews to provide additional information about the Goodson Rock Shelter assemblage's context and associations, as well as a more thorough luminescence analysis of the site's lowest deposits.